Effectiveness of Antioxidant Compounds in Swallow's Nest from Lombok - Juniawan, Alvin; Andini, Arista Suci; Wanadiatri, Halia (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study investigated the antioxidant activity of swallow nests known as Edible Bird Nests (EBNs) derived from the swallow species Collocalia linchi, especially those sourced from Lombok, Indonesia with various health benefits, including their potential as antioxidants. This study used swallow nest samples taken from 3 different locations, namely: East Lombok, Central Lombok and West Lombok. The extraction method used is heating and sonication. Antioxidant activity was assessed quantitatively using the DPPH method and measured by UV-Vis spectrophotometry. Results showed varying IC50 values across different extraction times, with the highest values recorded at 3818.47 mg/mL and the lowest at 2331.47 mg/mL, compared to the control (ascorbic acid) at 35.22 mg/mL. The higher the IC50 value, the lower the effectiveness of antioxidants and vice versa. These findings suggest that the antioxidant activity of EBNs extracts is relatively weak when compared to ascorbic acid. This study contributes to the understanding of optimized extraction techniques by heating and sonication to unlock the full potential of the extraction results of bioactive compounds.